Applying Computerized Adaptive Testing to the Desires for Speed Questionnaire in the Chinese Population: A Simulation Study. - Liu, Siyang; Guo, Xiaorong; Ma, Shihao; Chen, Qian; Wang, Weijun (Psychological Assessment, 2023)
The current methods for measuring patient-reported outcomes for amphetamine (speed) craving have limitation ability to adapt to the needs of individual patients while maintaining consistency in their scores. This study aimed to investigate whether the 40-item Desires for Speed Questionnaire (DSQ) could be improved for assessing clinical subjects using computerized adaptive testing (CAT). A sample of 677 participants from four drug addiction treatment centers in China was utilized in the study. Two types of analysis were conducted using the response data. First, the psychometric properties of all items were evaluated to meet the requirements of CAT. Second, multiple CAT simulations were carried out using real response data. The results indicated that the CAT method, which only required a small number of items (50%–75%), produced results that were only slightly different from the full DSQ assessment in terms of measuring amphetamine craving and criterion validity. In conclusion, this study suggests that developing a DSQ CAT for clinical subjects is useful as it leads to more efficient measurement without compromising the reliability of the test outcomes. Public Significance Statement: This study highlights the potential benefits of using computerized adaptive testing (CAT) to improve the efficiency and effectiveness of measuring amphetamine craving in clinical subjects. By reducing the number of items needed while maintaining reliability, this approach could ultimately lead to more personalized and targeted treatments for individuals with drug addiction.